Collagen Binding Proteins of Gram-Positive Pathogens - Arora, Srishtee; Gordon, Jay; Hook, Magnus (Frontiers in Microbiology, 2021)
Collagens are the primary structural components of mammalian extracellular matrices. In addition, collagens regulate tissue development, regeneration and host defense through interaction with specific cellular receptors. Their unique triple helix structure, which requires a Glycine residue every third amino acid, is the defining structural feature of collagens. There are 28 genetically distinct collagens in humans. In addition, several other unrelated human proteins contain a collagen domain. Gram-positive bacteria of the genera Staphylococcus, Streptococcus, Enterococcus and Bacillus express cell surface proteins that bind to collagen. These proteins of Gram-positive pathogens are modular proteins that can be classified into different structural families. This review will focus on the different structural families of collagen biding proteins of Gram-positive pathogen. We will describe how these proteins interact with the triple helix in collagens and other host proteins containing a collagenous domain and discuss how these interactions can contribute to the pathogenic processes.